If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = -3k + -2k Combine like terms: -3k + -2k = -5k 10 = -5k Solving 10 = -5k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '5k' to each side of the equation. 10 + 5k = -5k + 5k Combine like terms: -5k + 5k = 0 10 + 5k = 0 Add '-10' to each side of the equation. 10 + -10 + 5k = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 5k = 0 + -10 5k = 0 + -10 Combine like terms: 0 + -10 = -10 5k = -10 Divide each side by '5'. k = -2 Simplifying k = -2
| 3x+3+5x-7=28 | | 0,5z+6=z-1 | | 3x+1=7x+3 | | (6+u)(4u+5)=0 | | 5k-k=48 | | 4x(x-1)=(2x+5)(2x-5)+1 | | 3(f+2)=-15 | | 19=7+3y | | -15=n-3-5n | | -9m^2+11m-2+4m^2-8m+7= | | 7p+2p=99 | | 2(3t-5)=3t+15 | | -2a-6a=16 | | x(x+2)-13=(x-3)(x+3) | | x+3x+5x+2x+7= | | 56n^2+63=0 | | 2g+1=5 | | 3(2x-5y+4)= | | 6y+x=15 | | 4+(3)n=13 | | 11x=8x+27 | | 11x=6x+35 | | 7x=2x+45 | | 3(m-4)-(m+2)=0 | | 6(4x-7)=12 | | 6x^2+12x+4=0 | | 2(7x+2)=2x | | 3+3m+1=2m+4+m | | 7(8x-5)=21 | | 5n(12-2n)= | | n+12=20 | | 11x=5x+36 |